ANTIOXIDANT PROFILE AND PHYTOCHEMICAL CONTENT OF THREE KINDS OF LEMON GRASS GROWN IN WEST JAVA-INDONESIA - Kusmardiyani, Siti; Alfianti, Fitria; Fidrianny, Irda (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: The aims of this research were to determine antioxidant activity from various herbs extracts of three kinds of lemon grass using two antioxidant testing methods which were 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) and correlation of total phenolic content (TPC), total flavonoid content (TFC), and total carotenoid contents (TCC) with their inhibitory concentration 50% (IC ) of DPPH and exhibitory concentration 50% (EC 50 ) of FRAP. Methods: A sample was extracted by reflux method using different polarity solvents. The extracts were evaporated using rotary evaporator. Antioxidant activities using DPPH and FRAP assays, determination of TPC, TFC, and TCC were carried out by ultraviolet -visible spectrophotometry and correlation with their IC 50 of DPPH and EC 50 of FRAP capacities were analyzed by Pearson's method. Results: The ethanolic herbs extract of Cymbopogon citratus (CC) had the lowest IC 50 50 of DPPH scavenging activity 2.75 Âµg/ml and the lowest EC of FRAP capacity 12.22 Âµg/ml. Ethanolic herbs extract of Cymbopogon winterianus exposed the highest phenolic content and its n-hexane extract presented the highest carotenoid content. Ethyl acetate herbs extract of CC gave the highest flavonoid content. There was significantly negative correlation between TPC in CC herbs extract with their IC 50 of DPPH and EC 50 of FRAP. Conclusions: All herbs extracts from three kinds of lemon grass were categorized as a very strong antioxidant by DPPH method. Phenolic compounds in CC were the major contributor in antioxidant activities by DPPH and FRAP methods. DPPH and FRAP gave linear result in antioxidant activities of herbs extract of three kinds of lemon grass. Keywords: Antioxidant, 2,2-diphenyl-1-picrylhydrazyl, Ferric reducing antioxidant power, Lemon grass, Three kinds, Herbs. 50